1998
DOI: 10.1161/01.atv.18.2.235
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin I-Converting Enzyme Genotype Influences Arterial Response to Injury in Normotensive Rats

Abstract: Abstract-Two normotensive strains of rat, the Lou and Brown Norway (BN) strains, have contrasting levels of plasma angiotensin-converting enzyme (ACE). To investigate the degree of genetic determination of ACE expression, a polymorphic marker of the ACE gene was analyzed in inbred rats of the two strains. The two inbred strains were shown to bear different alleles for a polymorphic marker at the ACE gene. The segregation of the alleles of this marker and the plasma ACE levels were studied in a group of F2 rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
0
4

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 82 publications
7
35
0
4
Order By: Relevance
“…Animal models would be helpful to unravel these complex interactions in well-controlled experimental conditions. Therefore, we investigated the previously described difference between the B and L alleles (between the Brown Norway and Lou rats) (Challah et al 1998) and identified these alleles in the outbred Wistar rat. We bred two lines homozygous for the two alleles (called WU-B and WU-L) and determined their phenotype related to ACE in serum, heart, and kidney tissue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Animal models would be helpful to unravel these complex interactions in well-controlled experimental conditions. Therefore, we investigated the previously described difference between the B and L alleles (between the Brown Norway and Lou rats) (Challah et al 1998) and identified these alleles in the outbred Wistar rat. We bred two lines homozygous for the two alleles (called WU-B and WU-L) and determined their phenotype related to ACE in serum, heart, and kidney tissue.…”
Section: Discussionmentioning
confidence: 99%
“…These measurements showed clearly that both the ACE activity and mRNA expression were related to the B and L alleles and suggested that ACE activity is controlled at the transcriptional level. Challah et al (1998) …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…De façon analogue, les inhibiteurs du système rénine-angiotensine diminuent la prolifération intimale des cellules musculaires lisses secondaire à une angioplastie. Par ailleurs, le polymorphisme d'expression de l'enzyme de conversion influence le taux de resténose après angioplastie chez l'animal [28] comme chez l'homme [29]. Ces effets sont essentiellement dus à l'angiotensine II interstitielle, produite localement, au niveau des cellules musculaires lisses ou des fibroblastes, à partir de la rénine et de l'angiotensinogène adsorbés dans les tissus.…”
Section: Angiotensine II Et Fibroseunclassified